Health care system : a comparative study of Pakistan and Norway - Waeen, Zartash Arshad (Høgskolen i Bodø, 2007)
Mastergradsoppgave i bedriftsøkonomi - Høgskolen i Bodø, 2007 Abstract:- This study contributes the understanding and comparison of health care systems in developed and developing countries. For that purpose I decided to compare two politically and economically different countries like Norway and Pakistan. In addition, I attempt to contribute to the growing debate of health care system management and health institutions role in global world. The organisation of financing in a health care system has implications for the funding levels, rationing mechanisms, health service provision and expenditure. These criteria are the basis of comparison in this thesis. • Funding - In a public system, health care is funded from the general pool of all revenue collected through general taxation. • Rationing Mechanisms – Public health systems ration their resources through setting the pattern of supply, gate keeping, waiting lists and queues. . • Expenditure – Public systems commonly suffer from under-investment perhaps due to the funding dependent on the budget set by the government based on their assessment of the health care sector requirements. • Health Service Provision – In a public system, users cannot choose their GPs but are instead allocated one upon registration at a surgery. In addition users have to be referred by their GPs in order to see a specialist. The data for analysis was obtained from secondary sources of information. The main focus of collecting data was internet search, reference books and health journals.